Carrageenan From Kappaphycus alvarezii (Rhodophyta, Solieriaceae): Metabolism, Structure, Production, and Application - Rupert, Rennielyn; Rodrigues, Kenneth Francis; Thien, Vun Yee; Yong, Wilson Thau Lym (Frontiers in Plant Science, 2022)
Carrageenan is a polysaccharide derived from red algae (seaweed) with enormous economic potential in a wide range of industries, including pharmaceuticals, food, cosmetics, printing, and textiles. Carrageenan is primarily produced through aquaculture-based seaweed farming, with Eucheuma and Kappaphycus species accounting for more than 90% of global output. There are three major types of carrageenan found in red algae: kappa (κ)-, iota (ι)-, and lambda (λ)-carrageenan. Kappaphycus alvarezii is the most common kappa-carrageenan source, and it is primarily farmed in Asian countries such as Indonesia, the Philippines, Vietnam, and Malaysia. Carrageenan extracted from K. alvarezii has recently received a lot of attention due to its economic potential in a wide range of applications. This review will discuss K. alvarezii carrageenan in terms of metabolic and physicochemical structure, extraction methods and factors affecting production yield, as well as current and future applications.